Understanding quality of marriage among Malays - Abd Manaf, Abdul Razak; Harries, Maria; Clare, Mike (Centre for Promoting Ideas (CPI), 2011)
This qualitative research examines the perceptions of forty-five married Malay individuals about what they understand to be the ingredients of quality marital relationships. It utilised semi-structured interviews as a primary data-gathering instrument. In this paper, the researcher explains some of the reasons for the research question about quality of marital relationships, why the researcher decided to use a qualitative research design and how these interviews were conducted. Finally, this paper describes how the data are being analysed and identifies some issues that have arisen during this process.